2012
DOI: 10.1016/j.scitotenv.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of fertilization practices on human dietary intake of dioxins in Belgium

Abstract: Dioxins can enter the food chain at any stage, including crop fertilization. Therefore, we developed a simple method for estimating the introduction of dioxins in the food chain according to various fertilization practices. Using dioxin's contamination data taken from the literature, we estimated that fertilization accounts for approximately 20% of the dioxin inputs on agricultural soils at country scale. For the estimations at the field scale, 6 fertilization scenarios were considered: sludge, compost, digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our study confirmed that ash can scavenge organic pollutants from the atmosphere which, upon ash deposition, may promote contact with soil, vegetation and water where they then can be taken up in the food chain (Dumortier et al 2012). Ingestion of contaminated food represents the major route of human exposure to dioxins and dioxin-like compounds (Van den Berg et al 2006).…”
Section: Future Work Perspectivessupporting
confidence: 70%
“…Our study confirmed that ash can scavenge organic pollutants from the atmosphere which, upon ash deposition, may promote contact with soil, vegetation and water where they then can be taken up in the food chain (Dumortier et al 2012). Ingestion of contaminated food represents the major route of human exposure to dioxins and dioxin-like compounds (Van den Berg et al 2006).…”
Section: Future Work Perspectivessupporting
confidence: 70%
“…In addition, also animal manure contains approximately 0.6 ng TEQ/kg DM, which is potentially transferred to the food chain when spread on land (Dumortier et al 2012). The recycled ash mixture contains less than 5 ng TEQ per kg.…”
Section: Environmental Managementmentioning
confidence: 99%
“…This compared to a total atmospheric deposition on agricultural soils equivalent to approximately 33.6 g TEQ year −1 , which was approximately 6 times greater than the total input from fertilizer materials. Fertilization with compost containing PCDD/Fs at the maximum regulatory limit resulted in an input of 10.38 ng TEQ m , estimated in a study conducted by Dumortier et al [41], to prevent harmful dietary intakes of dioxins. Overall, therefore, the concentrations of PCDD/Fs and dioxin-like PCBs present in waste materials spread to land may represent a smaller contamination risk compared to other sources, such as atmospheric deposition [40].…”
Section: Dsmentioning
confidence: 99%
“…Venkatesan and Halden [41] analysed 12 PBDD/Fs in composited archived biosolids that were collected in 32 US States and the District of Columbia from 94 wastewater treatment plants as part of the US EPA national sewage sludge survey in 2001. Two PBDDs and five PBDFs were detected in the biosolids (all of which were detected in the present study), with a total mean concentration of 10,000 ng kg (Table 9), and were similar to the mean WHO2005-TEQ contribution observed by Venkatesan and Haldan [41] of 72 ng kg (Table 9). PBDD/Fs and PBBs may be present as impurities in commercial brominated flame retardants [42] which explains their presence in municipal biosolids and CLO derived from MSW.…”
Section: Polybrominated Dibenzo-p-dioxin (Pbdd) Dibenzofuran (Pbdf) mentioning
confidence: 99%